Dopamine infusion at typical infusion rates does not cause interference on plasma creatinine assays - Jenny Yeuk Ki Cheng; Shreenidhi Ranganatha Subramaniam; Stephanie C.Y. Yu; L.Y. Lois Choy; Jeffrey Sung Shing Kwok (Practical Laboratory Medicine, 2024)
a) Objectives: Dopamine is known to cause negative interference on enzymatic creatinine measurement. However, its effect on the Jaffe reaction, and its concentration required to interfere with enzymatic reactions, remain uncertain. This study was designed to study the interference of stable dopamine infusion on Jaffe and enzymatic creatinine assays, as well as the effect of dopamine infusion drip arm contamination on both creatinine assays. b) Design and Methods: For the first part of the study, dopamine was spiked into pooled plasma samples at different concentrations to mimic the scenario of patients on dopamine infusion at an infusion rate between 2 and 20 μg/kg/min. For the second part, dopamine preparation of 2 g/L (same as the preparation used clinically) was mixed with pooled plasma samples at different proportions to mimic drip arm contamination. Creatinine concentrations were measured using Jaffe and enzymatic reactions. c) Results: The first part showed that creatinine measurements were not interfered by dopamine infusion at an infusion rate between 2 and 20 μg/kg/min. The second part showed that dopamine could negatively interfere with enzymatic creatinine assays, even with minute drip arm contamination. The effect on the Jaffe reaction was less significant. d) Discussion: Creatinine concentration could be reliably measured by Jaffe or enzymatic reactions if samples are from venous access sites other than the site of dopamine infusion. When dopamine interference on enzymatic creatinine assays is suspected, using the Jaffe reaction to cross-check may provide additional useful information.